Copayments for ambulatory care in Germany: A natural experiment using a difference-in-difference approach - Jonas Schreyögg; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In response to increasing health expenditures and a high number of physician visits, the German government introduced a copayment for ambulatory care in 2004 for individuals with statutory health insurance (SHI). Because persons with private insurance were exempt from the copayments, this health care reform can be regarded as a natural experiment. We used a difference-in-difference approach to examine whether the new copayment effectively reduced the overall demand for physician visits and to explore whether it acted as a deterrent to vulnerable groups, such as those with low income or chronic conditions. We found that there was no significant reduction in the number of physician visits among SHI members compared to our control group. At the same time, we did not observe a deterrent effect among vulnerable individuals. Thus, the copayment has failed to reduce the demand for physician visits. It is likely that this result is due to the design of the copayment scheme, as the copayment is low and is paid only for the first physician visit per quarter.
Keywords: C13; I18; L31; 330; copayments; ambulatory care; difference-in-difference; count data; zero-inflated-model; Patienten; Konsumentenverhalten; Selbstbeteiligung (Versicherung); Gesetzliche Krankenversicherung; Ärzte; Wirtschaftspolitische Wirkungsanalyse; Deutschland